Macrophage polarization in response to epigenetic modifiers during infection and inflammation - Patel, Urmi (Drug Discov Today, 2016)
Macrophages are a heterogeneous population of phagocytic cells present in all tissues. Recently, several drugs that target the epigenetic machinery have emerged as attractive molecules for treating infection and inflammation by modulating macrophages. Treatment of lipopolysaccharide (LPS)-challenged macrophages with epigenetic modifiers leads to phenotype switching. This could provide stimulatory/destructive (M1) or suppressive/protective (M2) therapeutic strategies, which are crucial in the cytokine milieu in which the macrophages reside. In this review, we provide an overview of macrophage functional diversity during various diseases, including infection, as well as the current status in the development and clinical utility of epigenetic modifiers.